IMPLEMENTASI PROSES PEMUNGUTAN DAN KONTRIBUSI PENERIMAAN PAJAK AIR TANAH DI KABUPATEN MINAHASA SELATAN - Rorimpandey, Gabriela G.; Kalangi, Lintje; Lambey, Robert (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
This research aims to know and describe the implementation of groundwater tax collection process, obstacles and efforts made to determine these obstacles and calculate the amount of groundwater tax contribution in South Minahasa District conducted by the Regional Tax and Retribution Agency of South Minahasa Regency. This research is descriptive approach. The focus of this research is the application of the groundwater tax collection process, the obstacles and efforts undertaken to find out these barriers and the large contribution of ground water taxes. Based on the results of the research, the implementation of groundwater tax collection process in South Minahasa Regency has been conducted in accordance with the Law Number 28 Year 2009. However, the process of collecting ground water tax has not been done thoroughly in accordance with the provisions of the law. The obstacles are the people's unconsciousness over the ground water tax obligations, the arrears, the water meter has not been applied as a whole, and the business ambiguity inherent in the household. Efforts taken to overcome obstacles are socialization and a direct approach to the community, billing in the current month, installation of water meters and raising ground water prices. The contribution of groundwater taxes in the fiscal year 2014-2016 has increased, although for its contribution to local revenue slightly.Keyword: Ground Water Tax, Tax Collecting, Regional Tax, Contributions